2020
DOI: 10.1186/s12877-020-01790-7
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, skills and attitudes of older people and staff about getting up from the floor following a fall: a qualitative investigation

Abstract: Background Falls are the most common reason for ambulance callouts resulting in non-conveyance. Even in the absence of injury, only half of those who fall can get themselves up off the floor, often remaining there over an hour, increasing risk of complications. There are recognized techniques for older people to learn how to get up after a fall, but these are rarely taught. The aim of this study was to develop an understanding of attitudes of older people, carers and health professionals on getting up followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Although there is evidence of success in preventing falls with proactive exercise programming, some falls will inevitably still occur. Swancutt et al (2020) reveal three factors contributing to an individual's ability to get up from a fall: the environment, physical ability, and selfefficacy. Physical therapists (PTs) are healthcare providers with skills and knowledge to assess fall risk and deliver directed safe fall recovery (SFR) in-tive care services, or if the evaluating PT deemed the individual unsafe for study participation using the data collection instruments described in the procedural methods of this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is evidence of success in preventing falls with proactive exercise programming, some falls will inevitably still occur. Swancutt et al (2020) reveal three factors contributing to an individual's ability to get up from a fall: the environment, physical ability, and selfefficacy. Physical therapists (PTs) are healthcare providers with skills and knowledge to assess fall risk and deliver directed safe fall recovery (SFR) in-tive care services, or if the evaluating PT deemed the individual unsafe for study participation using the data collection instruments described in the procedural methods of this study.…”
Section: Methodsmentioning
confidence: 99%
“…Swancutt et al (2020) reveal three factors contributing to an individual's ability to get up from a fall: the environment, physical ability, and self-efficacy. Physical therapists (PTs) are healthcare providers with skills and knowledge to assess fall risk and deliver directed safe fall recovery (SFR) interventions in the home environment.…”
mentioning
confidence: 99%
“…With aging, falling can be considered as a risk factor, as well as the inability to rise up after a fall (Bloch, 2012;Bergen et al, 2016;CDC, 2022b). 50% of the seniors face difficulties in rising up after falling to the ground and most of them stay laying on the floor for >1 h, which may increase the risk of pressure sores, pneumonia, and even death (Swancutt et al, 2020). In a study conducted on 110 seniors, it was reported that 60% fell to the floor in which the majority fell at least twice (Fleming et al, 2008).…”
Section: Journal Of Disability Research 2023mentioning
confidence: 99%
“…With aging, falling can be considered as a risk factor, as well as the inability to rise up after a fall 3,4,9 . 50% of the seniors face difficulties in rising up after falling on the ground and most of them stay laying on the floor for more than one hour, which may increase the risk of pressure sores, pneumonia, and even death 10 . In a study conducted on 110 seniors, it was reported that 60% fell on the floor in which the majority fell at least twice 11 .…”
Section: Introductionmentioning
confidence: 99%